Geo-Navigasi di Museum: Aplikasi Realitas Tertambah di Museum Geologi Indonesia - Gozali, Alfian Akbar; Prawita, Fat'hah Noor; Gumilar, Ihshan; Ramdana Putra, Haidar Rashid; Fauzan, Muhammad Arief (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2024)
Navigational challenges in large buildings with multiple rooms, such as museums, often result in inefficient visitor experiences. Traditional signage and direction plans, while common, do not always effectively convey the necessary information. This paper introduces an innovative solution leveraging Augmented Reality (AR) technology to enhance navigation in such complex environments. We developed a mobile application utilizing the Immersal Software Development Kit (SDK) to facilitate interaction with the surroundings in the Bandung Geological Museum. The application serves as a digital guide, providing clear directions and route information to various rooms within the museum. Our study's findings reveal that the application not only facilitated easier navigation through its accurate room identification and route suggestions but also enhanced the overall visitor experience by making it more interactive and immersive. Furthermore, the user engagement and experience survey, encompassing a broad demographic range, highlighted a significant increase in visitor satisfaction and interaction. The application's intuitive and user-friendly interface played a key role in this enhanced engagement. The survey results reflect the application's success in meeting its main objectives, demonstrating usability, and offering an effective user interface.